Electronic reporting to improve patient safety. Issue 4 (2nd August 2004) - Tuttle, D; Holloway, R; Baird, T; Sheehan, B; Skelton, W K
Abstract : Background: Limited data are available on the experiences of voluntary event reporting systems to improve patient safety. Objective: Development and implementation of educational initiatives to facilitate the use of an electronic reporting system (ERS) in an academic medical center to measure the impact on knowledge of the ERS on reporting behavior and safety attitudes and to evaluate the accuracy of the information being reported. Methods: A voluntary internal confidential electronic system for reporting safety events was implemented which involved patients and visitors. A multifaceted educational program was developed to promote safety awareness and use of the ERS system. The safety event detail reported for the calendar year 2002 was tracked and trended and central event analyses were performed for five high event clinical areas. A survey was administered to assess safety knowledge and attitudes of patient care personnel. Results: 2843 safety events were entered into the ERS during 2002 with an increase during the course of the year (p = 0.055, linear trend) for all events. Nurses entered 73% of the events and physicians only 2%. 453 events (16%) were unsafe conditions or near misses and 623 (22%) were associated with patient harm. System factors were considered by the reporter as contributing to the event in only a few cases (5%). Central event analysis revealed that 39% of events had coding errors either in event classification, level of impact, or location; significant underreporting was also present. Although survey response rates were low (10.3%), responders showed a high degree of knowledge on general questions of patient safety and an increase in knowledge on use of the ERS (p = 0.0015, linear trend). Conclusions: Knowledge on the use of the reporting system and the frequency of reported events increased over the first year of the study. More work is needed to involve physicians in reporting, to improve the accuracy of submitted information, and to better prioritize, organize, and streamline event analysis.